If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2x + 24 = 0 Reorder the terms: 24 + 2x + 2x = 0 Combine like terms: 2x + 2x = 4x 24 + 4x = 0 Solving 24 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 4x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 4x = 0 + -24 4x = 0 + -24 Combine like terms: 0 + -24 = -24 4x = -24 Divide each side by '4'. x = -6 Simplifying x = -6
| x^2+18x+43=0 | | -22+20(p+20)=8-10(4p+22) | | 15/75=p/100 | | 2x-2x-24=0 | | f(x)=fx^2 | | 2/3(d)-2=4 | | 45+49/7*4 | | 2(b+2)-(7+b)=-5 | | 6(0)-8y=-48 | | -4(y+1.1)=3(y+3.9) | | 6x^2-xy-y^2-2x+y=0 | | 5=m/9 | | x=-32y^2 | | (4y+6)-(4+3y)=8 | | x-(-4)=16 | | h+3(h+4)=20 | | (2+i)(-7+5i)= | | 5(-8)+2y=8 | | 2x+2x-24=0 | | 5.7+1.7n=2.13 | | 2(X-3)=5(7-X) | | 12p=6(5p+7) | | (2+i)-(-7+5i)= | | 0=2x-13 | | m-(-2)=6 | | x^3-8x^2+9x+6=0 | | x=yx+2y | | -3(2x+4)+1=-13 | | 3y-5=3-2y | | y+4=-21 | | x-3(x+1)=9 | | -12x=-4+28 |